Specifics of contrastive teaching Russian as a foreign language (based on the example of Swahili) - Elena, Zharkova (2021)
The the article proves the crucial role of principles of comparative/contrastive teaching Russian. The author proves that Russian methodologists understand the need to take into consideration students' mother tongue when teaching Russian as a foreign language. The article contains general characteristics of Swahili and comparative analysis of Russian and Swahili lexical and grammatical systems as the basis for the system of teaching Russian as a foreign language.